Acid-Triggered Switchable Near-Infrared/Shortwave Infrared Absorption and Emission of Indolizine-BODIPY Dyes - Matthew A. Saucier; Cameron Smith; Nicholas A. Kruse; Nathan I. Hammer; Jared H. Delcamp (Molecules, 2023)
Fluorescent organic dyes that absorb and emit in the near-infrared (NIR, 700–1000 nm) and shortwave infrared (SWIR, 1000–1700 nm) regions have the potential to produce noninvasive high-contrast biological images and videos. BODIPY dyes are well known for their high quantum yields in the visible energy region. To tune these chromophores to the NIR region, fused nitrogen-based heterocyclic indolizine donors were added to a BODIPY scaffold. The indolizine BODIPY dyes were synthesized via microwave-assisted Knoevenagel condensation with indolizine aldehydes. The non-protonated dyes showed NIR absorption and emission at longer wavelengths than an aniline benchmark. Protonation of the dyes produced a dramatic 0.35 eV bathochromic shift (230 nm shift from 797 nm to 1027 nm) to give a SWIR absorption and emission (λmaxemis = 1061 nm). Deprotonation demonstrates that material emission is reversibly switchable between the NIR and SWIR.